Knowledge attitudes and practices of asthma; Does it associate with demographic factors of adult patients? - Madhushani H.P.D; Subasinghe H.W.A.S (Asian Pacific Journal of Health Sciences, 2016)
This study aimed to assess knowledge, attitude and practices of asthma and its associations with demographic factors in patients in a tertiary care-setting, Sri Lanka. A sample of 118 patients with asthma were enrolled for the study. Investigator administered, 44 item validated questionnaire was used to assess the cognitive variables of participants. Ethical approval was obtained from Ethics Review committee, Faculty of Medicine, University of Ruhuna. Data analysis performed using SPSS version 20. Overall knowledge about asthma was significantly higher (p=0.009) in females (11.75±2.39). The knowledge level was associated with patient’s age. Elderly patients above 51 years of age had low level knowledge (p<0.05) than patients between 31-50 years age. Patients who educated above grade 10 (12.07±2.43) had higher level of knowledge (p=0.001) about asthma compared to patients educated up to grade 5 (10.44±2.06). 64.4% of the sample had positive attitudes towards management of asthma. However, only 12.7% of the sample inhabit with good practices. Patient’s knowledge about asthma and its medication are associated with demographic factors of patients predominantly education level and age.